The Coherence Of Surah Al-Muzammil In Perspective Of Semitic Rhetoric Analysis (SRA) - Asnawi, Aqdi Rofiq; Rochmad, Rochmad; Munawar, Ali Mahfuz; Qonitatu, Isti (Civilization Research: Journal of Islamic Studies, 2025)
The aim of this research is to find the structure of Surah Al-Muzammil so that it can be seen whether the verses in it are coherent. This research method uses analysis, namely, to process data and answer research problems. The approach used in this literature research is Semitic Rhetorical Analysis (SRA) with descriptive analysis methods in data processing. The results of this research show that surah al-Muzammil is a text structure which is an application of SRA in surah al-Muzammil to produce a series consisting of 3 parts and 7 pieces which form a parallel concentric construction (A B/ x / A' B'). every piece and part have a relationship with other pieces and parts, so that every verse in surah al-Muzammil is interconnected. This finding was refuted by Richard Bell because each verse in surah al-Muzammil was able to be symmetrical with other verses from the lowest text level to the top text level, so this conclusion indicated that surah al-Muzammil was structured systematically and coherently.